2015
DOI: 10.3892/mmr.2015.4167
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C attenuates the toxic effect of aristolochic acid on renal tubular cells via decreasing oxidative stress-mediated cell death pathways

Abstract: Aristolochic acid (AA) is a component of Chinese medicinal herbs, including asarum and aristolochia and has been used in Traditional Chinese Medicine for a long time. Recent studies found that AA has a cytotoxic effect resulting in nephropathy. These studies indicated that AA‑induced cytotoxicity is associated with increases in oxidative stress and caspase‑3 activation. The present study further demonstrated that AA mainly elevates the H2O2 ratio, leading to increases in oxidative stress. Furthermore, the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…Growing evidence suggests that oxidative stress, tubular cell apoptosis, inflammation, and fibrosis are important pathogenic processes for AAN, although its detailed molecular mechanisms are still unclear [1,2]. Among them, oxidative stress is known to play an essential role in AA-induced cytotoxicity, because previous in vitro and in vivo studies have reported that AA treatment induces ROS generation and resultant oxidative injury [25][26][27]. In the present study, we performed IHC staining with a monoclonal antibody directed to 4-HNE, a product of lipid peroxidation, to detect oxidative injury.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that oxidative stress, tubular cell apoptosis, inflammation, and fibrosis are important pathogenic processes for AAN, although its detailed molecular mechanisms are still unclear [1,2]. Among them, oxidative stress is known to play an essential role in AA-induced cytotoxicity, because previous in vitro and in vivo studies have reported that AA treatment induces ROS generation and resultant oxidative injury [25][26][27]. In the present study, we performed IHC staining with a monoclonal antibody directed to 4-HNE, a product of lipid peroxidation, to detect oxidative injury.…”
Section: Discussionmentioning
confidence: 99%
“…A few in vitro studies described that cells treated with AA led to generation of high amounts of reactive oxygen and nitrogen species (ROS/RNS) [122,123,124,125]. Oxidative stress therefore constitutes the primary triggering event of AA cytotoxicity and could be responsible for related DNA damage through activation of the MEK/ERK1/2 signaling pathway and depletion of intracellular glutathione (GSH) [122] resulting in cell cycle arrest in G2/M phase [123].…”
Section: Properties Of Aa and Mechanisms Of Nephrotoxicity And Carmentioning
confidence: 99%
“…Oxidative stress therefore constitutes the primary triggering event of AA cytotoxicity and could be responsible for related DNA damage through activation of the MEK/ERK1/2 signaling pathway and depletion of intracellular glutathione (GSH) [122] resulting in cell cycle arrest in G2/M phase [123]. Treatment of the cells with antioxidants showed cytoprotective effects by reducing AA-induced ROS and genotoxicity, indicating that AA may induce DNA damage through oxidative stress [122,124]. Oxidative stress has also been described in in vivo models.…”
Section: Properties Of Aa and Mechanisms Of Nephrotoxicity And Carmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin C is another natural antioxidant compound. It has been reported that pretreatment with vitamin C exerted protective effects on NRK-52E treated with AA, through decreasing the high ratio of hydrogen peroxide (H 2 O 2 ) and caspase-3 activity generated by AA [92].…”
Section: Agents Exerting Antioxidative Effectsmentioning
confidence: 99%